A Real-Time Harmonic Detection Method for Single-Phase Active Power Filters - Emre Ozer (International Journal of Applied Methods in Electronics and Computers, 2016)
Abstract: Harmonics, due to the increasing use of nonlinear loads, such as converters and solid state switching devices, has become a serious problem in power systems. Active power filters (APFs) have been used effectively to eliminate harmonic components. Precision of harmonic detection is one of the most important factors of APFs. This paper describes a novel circuit is proposed for real-time harmonic detection as an alternative to conventional approaches. This circuit is based on a switched capacitor band-pass filter and a Phase Locked Loop (PLL) which has low distortion sine wave output. This PLL follows not only phase of reference signal but also its amplitude. Harmonic components have been obtained by subtracting produced fundamental component with PLL from distorted signal. Fundamental and harmonic components of distorted line voltage and current have been successfully separated experimentally.